AVERAGE SCORE OF THE UNIFIED STATE EXAMINATION - L. M. Nurieva; S. G. Kiselev (Образование и наука)
Introduction. Summing up the results of the Unified State Exam (USE) is traditionally based on comparing the average scores for institutions or territories, without taking into account what the indicator of the quality of education really represents.The aim of the article is to clarify the content «average score» on the example of the Mathematics federal testing results.Methodology and research methods. The methodology of comprehensive analysis is used, including the methods of comparative and statistical data analysis published following the exam results. As well, the parallel analysis of data used in the researches of the National Research University «The Higher School of Economics» (HSE) was conducted.Results and scientific novelty. It is found out that the average score in the Unified State Exam in mathematics largely depends on peculiarities of testing and assessment materials, a scoring system of leveling nature and results of training students for solving simple problems.Practical significance. The authors suppose that the study findings will contribute to the improvement of methods and technologies of carrying the Unified State Exam.